2018
DOI: 10.1016/j.redox.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Defective protein repair under methionine sulfoxide A deletion drives autophagy and ARE-dependent gene transcription

Abstract: ObjectiveReduction of oxidized methionines is emerging as a major protein repair pathway. The lack of methionine sulfoxide reductase A (MsrA) exacerbates cardiovascular disease phenotypes driven by increased oxidative stress. However, the role of MsrA on maintaining cellular homeostasis in the absence of excessive oxidative stress is less well understood.Methods and resultsConstitutive genetic deletion of MsrA increased formation of p62-containing protein aggregates, activated autophagy, and decreased a marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 67 publications
0
3
2
1
Order By: Relevance
“…Surprisingly, we found that both the Nrf2 and downstream HO‐1 expression levels were significantly decreased when MsrA was knocked down by msra siRNA (Figure 3I,L). These results differ from that of Pennington et al's findings, 39 which instead presented an increase in Nrf2, Keap1 and p62 expression in vascular smooth muscle cells from MsrA −/− mice, and in turn proposed that the abundant p62 competes with Nrf2 for binding to Keap1. However, we found an observable increase in Keap1 expression levels when MsrA was down‐regulated in EA.hy926 cells, suggesting that MsrA may be involved in the canonical step of Keap1‐mediated Nrf2 ubiquitination degradation.…”
Section: Discussioncontrasting
confidence: 99%
“…Surprisingly, we found that both the Nrf2 and downstream HO‐1 expression levels were significantly decreased when MsrA was knocked down by msra siRNA (Figure 3I,L). These results differ from that of Pennington et al's findings, 39 which instead presented an increase in Nrf2, Keap1 and p62 expression in vascular smooth muscle cells from MsrA −/− mice, and in turn proposed that the abundant p62 competes with Nrf2 for binding to Keap1. However, we found an observable increase in Keap1 expression levels when MsrA was down‐regulated in EA.hy926 cells, suggesting that MsrA may be involved in the canonical step of Keap1‐mediated Nrf2 ubiquitination degradation.…”
Section: Discussioncontrasting
confidence: 99%
“…3I and 3L). These results differ from that of Pennington et al's findings [40], which instead presented an increase in Nrf2, Keap1 and p62 expression in vascular smooth muscle cells from MsrA −/− mice, and in turn proposed that the abundant p62 competes with…”
Section: Discussioncontrasting
confidence: 99%
“…Wei-J et al reported that Ppp1r3b polymorphisms were associated with serum LDL-C levels, the risk of coronary artery disease and ischemic stroke in the Southern Chinese Han population 33 . The lack of Msra exacerbates cardiovascular disease phenotypes driven by increased oxidative stress 34 . Nevertheless, only Sox7 is related to cardiovascular development 12 , 16 , 17 .…”
Section: Discussionmentioning
confidence: 99%